2017
DOI: 10.1186/s13073-017-0415-3
|View full text |Cite
|
Sign up to set email alerts
|

Imiquimod has strain-dependent effects in mice and does not uniquely model human psoriasis

Abstract: BackgroundImiquimod (IMQ) produces a cutaneous phenotype in mice frequently studied as an acute model of human psoriasis. Whether this phenotype depends on strain or sex has never been systematically investigated on a large scale. Such effects, however, could lead to conflicts among studies, while further impacting study outcomes and efforts to translate research findings.MethodsRNA-seq was used to evaluate the psoriasiform phenotype elicited by 6 days of Aldara (5% IMQ) treatment in both sexes of seven mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
113
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(124 citation statements)
references
References 77 publications
(116 reference statements)
11
113
0
Order By: Relevance
“…Mouse back skin was treated with 62.5 mg 5% IMQ or a non-toxic cream once per day for five consecutive days. From the third day the erythema and scaling of IMQ-treated mice were observed which is similar to the reported study [12] (Figure 2(a)). Also the clinical score index is significant higher than control mice (Figure 2(b)).…”
Section: Imq-induced Psoriasis Animal Modelsupporting
confidence: 80%
See 4 more Smart Citations
“…Mouse back skin was treated with 62.5 mg 5% IMQ or a non-toxic cream once per day for five consecutive days. From the third day the erythema and scaling of IMQ-treated mice were observed which is similar to the reported study [12] (Figure 2(a)). Also the clinical score index is significant higher than control mice (Figure 2(b)).…”
Section: Imq-induced Psoriasis Animal Modelsupporting
confidence: 80%
“…In our study also revealed that the skin barrier protein filaggrin is reduced in the psoriasis patients, although as a long time impaired barrier function was regarded as a vital pathogenesis in atopic dermatitis (AD) [2]. In order to convince these results we use the IMQ-induced psoriasis mouse model [12]. IMQ is a TLR-7/8 agonist and [24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations